2023
DOI: 10.3389/fphar.2023.1105726
|View full text |Cite
|
Sign up to set email alerts
|

Xanthohumol alleviates oxidative stress and impaired autophagy in experimental severe acute pancreatitis through inhibition of AKT/mTOR

Abstract: Severe acute pancreatitis (SAP) is a lethal gastrointestinal disorder, yet no specific and effective treatment is available. Its pathogenesis involves inflammatory cascade, oxidative stress, and autophagy dysfunction. Xanthohumol (Xn) displays various medicinal properties,including anti-inflammation, antioxidative, and enhancing autophagic flux. However, it is unclear whether Xn inhibits SAP. This study investigated the efficacy of Xn on sodium taurocholate (NaT)-induced SAP (NaT-SAP) in vitro and in vivo. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Xanthohumol (Xn), a natural prenylated chalcone compound isolated from hops, restored autophagy flux by inhibiting the AKT/mTOR pathway in experimental pancreatitis. This was associated with reductions in necrosis, inflammation, oxidative stress, and the severity of pancreatitis [384]. Experiments also indicated that Pancreatic Protein kinase C iota (PKCi) significantly increased pancreatic immune cell infiltration, acinar cell DNA damage, and apoptosis, but reduced sensitivity to cerulein-induced pancreatitis.…”
Section: Autophagy In Pancreatitismentioning
confidence: 97%
See 1 more Smart Citation
“…Xanthohumol (Xn), a natural prenylated chalcone compound isolated from hops, restored autophagy flux by inhibiting the AKT/mTOR pathway in experimental pancreatitis. This was associated with reductions in necrosis, inflammation, oxidative stress, and the severity of pancreatitis [384]. Experiments also indicated that Pancreatic Protein kinase C iota (PKCi) significantly increased pancreatic immune cell infiltration, acinar cell DNA damage, and apoptosis, but reduced sensitivity to cerulein-induced pancreatitis.…”
Section: Autophagy In Pancreatitismentioning
confidence: 97%
“…Restoration of autophagy. Reduction of pancreatitis severity [384] ER stress Activation of trypsinogen and impaired autophagy [402][403][404]407] ROS overproduction Mitophagy disruption. Activation of AKT/mTOR pathway.…”
Section: Original Studies Outcomes Referencesmentioning
confidence: 99%